JUAL BELI PADI TEBASAN DENGAN SISTEM CENGKLONG KAJIAN: PERSPEKTIF MASHLAHAH MURSALAH - Deby Lionika; Nastangin Nastangin (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
The sale and purchase of slashed rice with the cengklong system in Sranten Village, Karanggede District, Boyolali Regency is carried out by farmers and slashers where in the sale and purchase there is a price change that has been agreed at the beginning. This price change occurred due to the quality of rice is not good so that after all the rice was cut down and weighed the results did not match the initial prediction. Therefore, the slasher mencengklong the farmer's rice price that had been agreed at the beginning. The type of this research is field research, using a qualitative descriptive method with an empirical juridical approach. The theory used in this research is maslahah mursalah. Data collection techniques with the method of observation, interviews and documentation. The results of this research are the sale and purchase of slashed rice with the cengklong system in Sraten Village, Karanggede District, Boyolali Regency, the perspective of mashlahah mursalah has more benefits than madharot. The benefits are that the slasher can help farmers to buy their rice quickly, farmers don't need to rent rice cutting tools, the services of people to pick rice and transportation costs are all from the slasher, farmers can help the slasher by buying the rice and then selling it back to selep (the rice grinder) place, if there is a problem or madharat regarding the price of rice in cengklong slasher and farmers resolve it amicably and through deliberation so that they are mutually pleased with each other.